2017
DOI: 10.1177/1938640017750258
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Motion: Patient-Reported Outcome Measures Are Correlated With Range of Motion in Total Ankle Replacement

Abstract: Level III: Retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…This is similar to previous studies which have demonstrated significant improvements in PROs following TAR. 1,9,13,24,27,33,38 Despite the lower preoperative scores among the female cohort, the magnitude of improvement was equivalent among men and women with the exception of SF-36 physical function scores, which was significantly greater in men. Interestingly, Cherian et al also noted the SF-36 physical component was significantly better in men at multiple time points following TKA.…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 92%
See 1 more Smart Citation
“…This is similar to previous studies which have demonstrated significant improvements in PROs following TAR. 1,9,13,24,27,33,38 Despite the lower preoperative scores among the female cohort, the magnitude of improvement was equivalent among men and women with the exception of SF-36 physical function scores, which was significantly greater in men. Interestingly, Cherian et al also noted the SF-36 physical component was significantly better in men at multiple time points following TKA.…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 92%
“…Previous studies have found that although all patients demonstrated significant improvement in PROs following TAR, no differences were observed between the different types of prostheses used. 9,32 The preoperative differences between male and female patients included significantly worse preoperative scores for SF-36 total, SF-36 mental health component, AOFAS total, AOFAS pain, SMFA function, and SMFA bother scores among women. When controlling for potential confounding variables including inflammatory arthritis and other factors disparate between the 2 genders (primary diagnosis, age, former tobacco use, prosthesis), female gender remained an independent risk factor for worse preoperative scores.…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 99%
“…1,12,16,19,[24][25][26]28 Range of motion was assessed radiographically using previously published methods of isolating tibiotalar motion after total ankle replacement. 7,8 Radiographic preoperative assessment of range of motion was not available for all patients; we did not begin adding this assessment to our routine preoperative radiographic assessment of patients with end-stage ankle arthritis until after the initiation of this investigation. Measurements were performed using the Phillips PACS picture archive and communication system (Phillips Healthcare, Andover, MA).…”
Section: Methodsmentioning
confidence: 99%
“…8,13 Furthermore, studies have shown that the amount of ankle range of motion obtained following replacement is positively correlated with a patient’s reported outcome measures. 5…”
Section: Introductionmentioning
confidence: 99%